Small and Medium Enterprises: Importance for the Kosovo Economy - Loku, Afrim; Loku, Nadire; Baftiu, Naim (Technium Social Sciences Journal, 2021)
This study aims to broaden the understanding of the importance of SMEs (Small and Medium Enterprises) for the economy of Kosovo, especially in terms of economic development, labor market and innovation. The study was conducted through analysis of documentary sources such as relevant reports of national and international institutions as well as relevant scientific papers. The scientific contribution of this study is theoretical and aims to help researchers of the field for an expanded understanding of SMEs over national economies. This study provides a concise framework of important elements on the economic impact of SMEs on Kosovo’s economy. Examination of available data has shown that the SME sector plays a crucial role for the Kosovo economy. The key role of SMEs was emphasized in terms of overall value generated and the labor market while innovation remains a challenge to be addressed by stakeholders. Website: https://uni-pr.edu